2015
DOI: 10.1021/acs.jpca.5b06678
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Water–Ethanol Solutions: The Estimation of Hydrogen Bonding Energy and the Appearance of Clathrate-like Structures in Solutions

Abstract: The structure of aqueous alcohol solutions at the molecular level for many decades has remained an intriguing topic in numerous theoretical and practical investigations. The aberrant thermodynamic properties of water-alcohol mixtures are believed to be caused by the differences in energy of hydrogen bonding between water-water, alcohol-alcohol, and alcohol-water molecules. We present the Raman scattering spectra of water, ethanol, and water-ethanol solutions with 20 and 70 vol % of ethanol thoroughly measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 60 publications
11
91
0
Order By: Relevance
“…[3] The preferentialh ydration of ap rotein in the presenceo fc osolvents may be regardeda saresult of the delicate balance of three different contributions:arepulsion and an attraction between the protein andc osolventa nd the steric exclusion of the cosolvents acting as classical" crowders". [7][8][9][10][11][12][13][14][15][16][17][18][19] It has been concluded that the conventional "iceberg" modeli sn ot appropriate to explain the experimental resultsa nd that the presence of hydrophobic moieties on the alcohol are responsible for the unusual rotational mobility of water. [4][5][6] Anomaloush ydration behavior of alcohols hasb een studied extensively by using variouse xperimental and simulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The preferentialh ydration of ap rotein in the presenceo fc osolvents may be regardeda saresult of the delicate balance of three different contributions:arepulsion and an attraction between the protein andc osolventa nd the steric exclusion of the cosolvents acting as classical" crowders". [7][8][9][10][11][12][13][14][15][16][17][18][19] It has been concluded that the conventional "iceberg" modeli sn ot appropriate to explain the experimental resultsa nd that the presence of hydrophobic moieties on the alcohol are responsible for the unusual rotational mobility of water. [4][5][6] Anomaloush ydration behavior of alcohols hasb een studied extensively by using variouse xperimental and simulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…At the same relative membrane depth, the fractional presence of water is ~0.2, indicative of an 80% reduction of H-bonding donor presence in this environment. Interestingly, the H-bond enthalpy in pure ethanol is also ~80% reduced compared to pure water 19 . Together, this suggests that the negatively charged MC moiety is well inserted into the interfacial region of the bilayer, slightly above the carbonyl moieties of the FA esters.…”
Section: Resultsmentioning
confidence: 98%
“…The time‐domain IR spectroscopy measures the H–O bond relaxation or lifetime in terms of solution molecular delocalization dynamics that determines the viscosity of the solution. Complementing the SFG vibrational and time‐domain IR spectroscopy, Raman spectroscopy and the derived differential Raman spectra (DRS) probes the information of the O:H–O bond cooperative relaxation as the Raman wavenumber shift ω x are determined uniquely by the segmental length d x and energy E x , irrespective to the nature of the stimulation sources or the incident photon energy ωHtrue/LEH/L/μH/LdH/L()kHtrue/L0.5em+0.5emkCdH/L where μ H / L is the reduced mass for H–O and O:H, respectively; the specific x oscillator; and k H / L and k C are the force constants or the second differentials of the intramolecular/intermolecular interaction and O–O Coulomb coupling potentials.…”
Section: Principlesmentioning
confidence: 99%
“…Infrared absorption, Raman scattering, neutron scattering, X‐ray scattering, sum frequency generation (SFG) vibrational spectroscopy, Brillouin, and nuclear magnetic resonance spectroscopy (NMR), and molecular dynamic (MD) simulation have been elegantly used for investigating how the hydroxyl and hydrocarbon groups interact with the solvent water and how they functionalize the water hydrogen bond network. Li and coworkers studied the structure and dynamics of alcohol solutions by terahertz and PFG‐NMR techniques.…”
Section: Introductionmentioning
confidence: 99%